1992
DOI: 10.1128/mcb.12.7.3288
|View full text |Cite
|
Sign up to set email alerts
|

Topology and functional domains of Sec63p, an endoplasmic reticulum membrane protein required for secretory protein translocation.

Abstract: ). Antibody directed against a recombinant form of the protein detects a 73-kDa polypeptide which, by immunofluorescence microscopy, is localized to the nuclear envelope-ER network. Cell fractionation and protease protection experiments confirm the prediction that Sec63p is an integral membrane protein. A series of SEC63-SUC2 fusion genes was created to assess the topology of Sec63p within the ER membrane. The largest hybrid proteins are unglycosylated, suggesting that the carboxyl terminus of Sec63p faces the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
198
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(212 citation statements)
references
References 53 publications
14
198
0
Order By: Relevance
“…Consistent with this, the GFP flouorescence in this region overlapped with red fluorescence from RFP-tagged Sec63p (Fig. 3b) , a protein known to localise to the ER (Feldheim et al, 1992). In addition to the ER, GFP signal was also observed in optically bright regions connecting to the ER ( Fig.…”
Section: The C-terminal Of Erg9p Is a Signal Peptide Targeting The Ensupporting
confidence: 74%
See 1 more Smart Citation
“…Consistent with this, the GFP flouorescence in this region overlapped with red fluorescence from RFP-tagged Sec63p (Fig. 3b) , a protein known to localise to the ER (Feldheim et al, 1992). In addition to the ER, GFP signal was also observed in optically bright regions connecting to the ER ( Fig.…”
Section: The C-terminal Of Erg9p Is a Signal Peptide Targeting The Ensupporting
confidence: 74%
“…Fluorescent microscopy showed that GFP was located in the perinuclear/peripheral organelles, a region recognised as the ER (Feldheim et al, 1992). Consistent with this, the GFP flouorescence in this region overlapped with red fluorescence from RFP-tagged Sec63p (Fig.…”
Section: The C-terminal Of Erg9p Is a Signal Peptide Targeting The Ensupporting
confidence: 72%
“…The expectation that additional proteins are involved has been nourished by the observation that in E. coli the Hsp70 homolog, DnaK, acts in concert with two other heat shock proteins, DnaJ and GrpE (reviewed by Georgopoulos, 1992). Furthermore, in S. cerevisiae, the Hsp70 homologs Ssalp and Kar2p are thought to interact with the DnaJ homologs Ydjl p and Sec83p, respectively (CapIan et al, 1992;Sadler et al, 1989;Feldheim et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…These results point to a new functional assignment for p58 IPK in serving as a BiP cochaperone to optimize protein folding homeostasis in the ER. Because p58 IPK represents one among several (at least five others) ER localized Jdomain proteins that interface with BiP (Feldheim et al, 1992;Brightman et al, 1995;Shen et al, 2002;Hosoda et al, 2003;Shen and Hendershot, 2005), its absence would result in an ER lumen that is only modestly compromised in overall folding capacity. The functional consequences of this slightly lower protein maturation capacity would be obscured under all but the most taxing conditions and can explain each of the following phenotypic observations in cells and animals lacking p58 IPK .…”
Section: Discussionmentioning
confidence: 99%